Chameleonizing - Dahl, Johanne Yttri (European journal of criminology, 2022)
This study empirically explores covert physical surveillance conducted by the police and proposes the concept of chameleonizing in covert physical surveillance. Like the chameleon, police officers conducting covert physical surveillance must blend into and mirror their surroundings by adapting their appearance, in terms of both looks and behaviour, to resemble the people in the vicinity to prevent detection. Thus, police officers conducting covert physical surveillance must be able to read their surroundings and have great knowledge about social interactions. Accordingly, this exploration of an extraordinary phenomenon, covert physical surveillance, sheds light on something very ordinary: that is, social interactions in everyday life. Furthermore, the concept of the chameleon gaze is proposed and discussed, because physical surveillance depends on a multifaceted gaze enabling observation from different angles.